(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2019)
A new collection of ammonites from the Picunleufuense Zone (standard base of the Andean Tithonian) of the locality Estancia María Juana (southern Neuquén Basin, Argentina) has provided abundant and well preserved material of new transients of Indansites picunleufuense and Choicensisphinctes platyconus. These transients are described and a detailed review of the early evolution of the Indansites lineage is presented. The meaning of changes in rib density, variations within the microconchs (males) and the length of the bodychamber in Indansites picunleufuense are discussed. It is concluded that the changes in rib density which characterize the successive macroconchs of the transients indicate changes in the rate of shell-growth. The more densely ribbed phragmocone of later transients would have had lower growth rates, which would also explain their smaller adult size. The microconchs show high variation in adult size suggesting high plasticity in the size-age maturation, most likely caused by influence of seasonal environmental conditions. A large small-macroconch-like lapetted microconch, coming from the close locality Picún Leufú, is interpreted as a new case of sex-change.